DIGITAL MEDICINE FOR HEALTH CARE SYSTEM - MR.SHREEKRUSHN GHODAKE; MR.SURAJ SURVASE; MR.ONKAR HIREMATH (International Journal of Innovations in Engineering Research and Technology, 2021)
Currently, the scenario is such that the patient who’s suffering from any disease has to go to the doctor’s clinic in order to book an appointment. There is no such software that can tell the patient what disease he/she is suffering from based on the symptoms given. Similarly the software nowadays don’t give you the option of finding a doctor based on the location or may be on his name or may be on the specialty.Similarly for the doctor, the doctors ask the patients to get their prescriptions when they come for the next appointment. The doctors don’t keep track of when the patient appeared last to him/her did. The doctors don’t even know who they are going to visit for the day so that they can manage their appointments according to that. Efficient doctor patient portal is a managing system that helps doctors as well as the patients by providing options of booking appointments as per the convenience of both doctor and patients with the motive of medical progress. Through this system, doctors can easily manage the appointment slots.software and it is developed for Social Welfare office and NGO’S. To send Applicable Benefits Detail information through SMS.